2015
DOI: 10.1016/j.ijplas.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of ultrafine-grained/nanocrystalline titanium synthesized by mechanical milling plus consolidation: Experiments, modeling and simulation

Abstract: High quality bulk ultrafine-grained/nanocrystalline titanium samples were prepared through room temperature mechanical milling and conventional consolidation processes. The prepared bulk samples showed high purity, very low porosity and high ductility under compression. The dependency of yield stress and post-yielding behavior on grain size, strain rate and temperature were comprehensively studied. The texture evolution of the ufg/nc samples under compression was measured by synchrotron XRD. On the macroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 55 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…Creep is time-dependent plastic deformation in the materials under constant load or stress, specifically observed at higher homologous temperature (Khan and Zhang, 2001;Liu et al, 2015). Creep deformation in metal is generally induced by the dislocation generation, motion and annihilation (Basirat et al, 2012).…”
Section: Creep Mechanismmentioning
confidence: 99%
“…Creep is time-dependent plastic deformation in the materials under constant load or stress, specifically observed at higher homologous temperature (Khan and Zhang, 2001;Liu et al, 2015). Creep deformation in metal is generally induced by the dislocation generation, motion and annihilation (Basirat et al, 2012).…”
Section: Creep Mechanismmentioning
confidence: 99%
“…Moreover, the ductility after ECAP was in the 10-20% range, which is sufficient for structural application. The ECAP alone may not result is requisite refine as reported in the latest literature [18]. Jian et al (2015) reported that the strength of ECAPed pure Ti was lower and merely at par with that of Ti-6Al-4V alloy.…”
Section: Effect Of Ecap On Mechanical Propertiesmentioning
confidence: 95%
“…Jian et al (2015) reported that the strength of ECAPed pure Ti was lower and merely at par with that of Ti-6Al-4V alloy. The limited enhancement in strength related to the limited grain size refining capability of the ECAP alone [18]. A large number of investigations are being carried out to further enhance the strength by superposing cold working or SPD processes after the ECAP processing on CP Ti.…”
Section: Effect Of Ecap On Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, constitutive equations taking into account the grain size of metal alloys were offered by Meyers et al [4,18], Armstrong and Zerilli [30], and Khan et al [31,32]. Mishra et al modified the model of Johnson-Cook [33].…”
Section: The Constitutive Equation For Ultrafine-grained Alloys Covermentioning
confidence: 99%